2020
DOI: 10.1016/j.ctim.2019.102229
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary and alternative medicine in patients with chronic viral hepatitis in Turkey

Abstract: Introduction: The global use of complementary and alternative medicine (CAM) is growing. The purpose of this study was to determine the prevalence of CAM use in patients in Turkey with CVH, the types of therapy, and patients' sociodemographic characteristics. Methods: The study was designed as a questionnaire-based, cross-sectional analysis. An infectious diseases outpatient follow-up questionnaire was administered to patients at face-to-face interviews. The data obtained were analyzed using SPSS 17 software. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 19 publications
1
19
0
1
Order By: Relevance
“…We note that the prayer is included in integrative medicines in the Turkey. This results may be explained in connection with the fact that religious values like prayer has a significant place in Turkish culture and society 38,39 . It should also be evaluated whether patients using these methods continue pharmacological treatment and whether they benefit or harm from these methods 12 .…”
Section: Discussionmentioning
confidence: 94%
“…We note that the prayer is included in integrative medicines in the Turkey. This results may be explained in connection with the fact that religious values like prayer has a significant place in Turkish culture and society 38,39 . It should also be evaluated whether patients using these methods continue pharmacological treatment and whether they benefit or harm from these methods 12 .…”
Section: Discussionmentioning
confidence: 94%
“…In a study involving 1112 people, a significant relationship was found between the honey consumption and education levels of the participants (Tunca et al, 2015). In a study, it was determined that the level of education is important in using the complementary alternative medicine (Ince et al, 2020). It is important that nurses take responsibility for the apitherapy method included in complementary and alternative medicine methods and that nurses can use evidence-based apitherapy methods.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Many viruses can cause hepatitis, including herpes simplex virus (HSV), cytomegalovirus (CMV), Epstein-Barr virus (EBV), and others. 41 Lemoine et al 42 suggested that strategies for a global approach include the implementation of operational and research programs, the improvement of screening and diagnosis tools, broader access to treatment and the integration of prevention, screening and care for viral hepatitis in local health care systems.…”
Section: -28mentioning
confidence: 99%